El modelo osar como estrategia didáctica para el aprendizaje de ondas en los estudiantes de tercer año de bachillerato general unificado paralelo B, del colegio Pío Jaramillo Alvarado de la ciudad de Loja, período 2015-2016 - Pogo Agila, Ramiro Favian (2015)
The research aims to consider HOW OSAR MODEL LEARNING TEACHING STRATEGY OF WAVES IN THE THIRD YEAR STUDENTS OF GENERAL UNIFIED PARALLEL HIGH SCHOOL B SCHOOL Pío Jaramillo Alvarado Loja, PERIOD 2015-2016. The overall objective is proposed as follows: apply the OSAR model as a teaching strategy to enhance learning waves. The research process answered a descriptive design (diagnosis) and experimental pre. The phases were fulfilled in their order were: comprehensive, which involved perceive, explain causes and effects on students; diagnostic, he allowed the current situation of the school Pío Jaramillo Alvarado to discover problems in students; modeling, a model was created to investigate the reality; Application served to get the right process and achieving the goal set previously; and valuation allowed to determine the effectiveness of the OSAR model as a teaching strategy for learning waves. A large majority of students indicate difficulties, obstacles and gaps in learning the definition of wave. Students have melt when using formulas to find the speed that the longitudinal and transverse waves propagate. Teachers can apply the OSAR model as a teaching strategy to improve academic performance